2019
DOI: 10.1002/ecs2.2773
|View full text |Cite
|
Sign up to set email alerts
|

Are we approaching a water ceiling to maize yields in the United States?

Abstract: While annual precipitation in much of the US Corn Belt is likely to remain constant, atmospheric vapor pressure deficit (VPD), the driver of crop water loss (evapotranspiration; ET), is projected to increase from~2.2 kPa today to~2.7 kPa by mid-century primarily due to the temperature increase. Without irrigation, it has been hypothesized that the increase in VPD will create a ceiling to future increases in maize yields. We calculated current and future growing season ET based on biomass, water use efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 46 publications
1
47
2
Order By: Relevance
“…Taken together these results demonstrate that enhanced iWUE is achieved either through low g s or through coupling high A N with moderate g s . While in the past it was suggested that WUE across C 4 species was almost invariant (DeLucia et al, 2019), this study builds on work in sugarcane (Inman-Bamber et al, 2016) to suggest that meaningful variation does exist. Our generalized estimates of heritability for A N and g s (Figure 5) were similar to those estimated in a recent survey of the same traits in a smaller panel of grain sorghum accessions (Ortiz et al, 2017) and sufficiently high to justify targeting them as traits for selection.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Taken together these results demonstrate that enhanced iWUE is achieved either through low g s or through coupling high A N with moderate g s . While in the past it was suggested that WUE across C 4 species was almost invariant (DeLucia et al, 2019), this study builds on work in sugarcane (Inman-Bamber et al, 2016) to suggest that meaningful variation does exist. Our generalized estimates of heritability for A N and g s (Figure 5) were similar to those estimated in a recent survey of the same traits in a smaller panel of grain sorghum accessions (Ortiz et al, 2017) and sufficiently high to justify targeting them as traits for selection.…”
Section: Discussionmentioning
confidence: 90%
“…The trade-off between carbon gain and water use is a fundamental constraint for crop productivity and environmental resilience (Bailey-Serres et al, 2019; DeLucia et al, 2019; Leakey et al, 2019). More specifically, improving WUE is recognized as a means to enhance the utility of sorghum as a biofuel feedstock (Mathur et al, 2017; Meki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiotemporal variations in the irrigation effect found in our results highlight the strong influence of background climate conditions. With projected shifting precipitation patterns and more frequent droughts and heatwaves in the future (Huang et al, ; Wuebbles et al, ), a large expansion of irrigation would be required to sustain current maize yield trends in the United States (DeLucia et al, ; McDonald & Girvetz, ). Within this context, irrigation effects are expected to be intensified, leading to a greater synergistic effect of crop yield increase and cooling benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that corn in the Midwest will require ~35% more water inputs to reach yield targets by 2050 20 , 21 , arguing that sustaining yield gains will not be feasible without widespread expansion of irrigation infrastructure 22 . This claim is questionable, in part due to evidence showing that large differences in crop biomass and yield can be achieved with the same amount of ET, both within and across species with similar growing-season length 14 , 23 .…”
Section: Introductionmentioning
confidence: 99%